Junji ito's cat diary: yon & mu, volume 1 ebook - Ito, Junji (Junji Ito's Cat Diary: Yon & Mu, 2015)
HELL-O-KITTY Master of Japanese horror manga Junji Ito presents a series of hissterical tales chronicling his real-life trials and tribulations of becoming a cat owner. Junji Ito, as J-kun, has recently built a new house and has invited his financée, A-ko, to live with him. Little did he know…his blushing bride-to-be has some unexpected company in tow—Yon, a ghastly-looking family cat, and Mu, an adorable Norwegian forest cat. Despite being a dog person, J-kun finds himself purrsuaded by their odd cuteness and thus begins his comedic struggle to gain the affection of his new feline friends.